Studi Penelitian Panjang Kritis Serat Alam Dengan Perlakuan Perendaman Natrium Hidroksida - Rangga Yanuarestu Ramadhan; Yuyun Estriyanto; Budi Harjanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
The purpose of this study was to determine the critical length of palm fiber, kenaf fiber, pineapple fiber, agave fiber, and coconut fiber with NaOH immersion treatment. This study was determine the effect of NaOH immersion treatment on the critical length of fiber. This research is an experimental exploratory research. The independent variables in this study were palm fiber, kenaf fiber, pineapple fiber, agave fiber, and coconut fiber with the dependent variable is the critical fiber length. To find the critical length of fiber using single fiber tensile test and single fiber pull out test. The data obtainde from the test results are then analyzed using formula equation to determine the critical length of each fiber. Data analysis techniques using quantitative descriptive analysis techniques. The results showed that the critical length of palm fiber, kenaf fiber, agave fiber, and coconut fiber with NaOH immersion treatment was shorter than the critical length of fiber without NaOH immersion treatment. Agave fiber has the shortest critical fiber length. The critical length of the fiber with NaOH immersion treatment are palm fiber 4.6 mm, kenaf fiber 5.4 mm, pineapple fiber 3.6 mm, agave fiber 2.2 mm, and coconut fiber 3.0 mm.